Pneumoretroperitoneum with subcutaneous emphysema after a post colonoscopy colonic perforation - Jaafar, Sahned (Int J Surg Case Rep, 2019)
INTRODUCTION: Colonoscopy is considered as one of the most common performed procedures for both diagnostic and therapeutic purposes. Serious complication after colonoscopy could occurs like bleeding or perforation. Majority of the perforations are intraperitoneal, while extraperitoneal perforations are very rare and it may cause pneumoretroperitoneum, pneumomediastinum, pneumothorax and subcutaneous emphysema. PRESENTATION OF THE CASE: A case report was described of 80-year-old female who underwent a diagnostic colonoscopy for recurrent abdominal pain who presented with severe abdominal pain and tenderness with CT findings of pneumoperitoneum, pneumoretroperitoneum and subcutaneous emphysema. The patient successfully treated surgically with laparoscopic Hartman procedure. DISCUSSION: Colonic perforation is rare complication of colonoscopy that can manifest intraperitoneal, extraperitoneal or a combination of both. Patient risk factors include advance age, female sex, diverticulosis, previous abdominal surgery and pre-existing colonic strictures. Technical risk factors includes excessive shearing forces during endoscopic insertion, dilation, biopsy and using electrocautery. Majority of the intraperitoneal perforation warrant a surgical intervention whereas isolated extraperitoneal perforation may be managed conservatively. CONCLUSION: Combined intraperitoneal and extraperitoneal colonic perforation are rare presentations following diagnostic colonoscopy and often difficult to diagnose based on the clinical manifestation only. Understanding the manifestation of extraperitoneal perforation will help to properly identify the condition and preventing morbidity and mortality in these patients.